Glacier Changes in Iceland From ∼1890 to 2019 - Aðalgeirsdóttir, Guðfinna; Magnússon, Eyjólfur; Pálsson, Finnur; Thorsteinsson, Thorsteinn; Belart, Joaquín M. C.; Jóhannesson, Tómas; Hannesdóttir, Hrafnhildur; Sigurðsson, Oddur; Gunnarsson, Andri; Einarsson, Bergur; Berthier, Etienne; Schmidt, Louise Steffensen; et al. (Frontiers in Earth Science, 2020)
The volume of glaciers in Iceland (∼3,400 km3 in 2019) corresponds to about 9 mm of potential global sea level rise. In this study, observations from 98.7% of glacier covered areas in Iceland (in 2019) are used to construct a record of mass change of Icelandic glaciers since the end of the 19th century i.e. the end of the Little Ice Age (LIA) in Iceland. Glaciological (in situ) mass-balance measurements have been conducted on Vatnajökull, Langjökull, and Hofsjökull since the glaciological years 1991/92, 1996/97, and 1987/88, respectively. Geodetic mass balance for multiple glaciers and many periods has been estimated from reconstructed surface maps, published maps, aerial photographs, declassified spy satellite images, modern satellite stereo imagery, and airborne lidar. To estimate the maximum glacier volume at the end of the LIA, a volume–area scaling method is used based on the observed area and volume from the three largest ice caps (over 90% of total ice mass) at 5–7 different times each, in total 19 points. The combined record shows a total mass change of −540 ± 130 Gt (−4.2 ± 1.0 Gt a−1 on average) during the study period (1890/91 to 2018/19). This mass loss corresponds to 1.50 ± 0.36 mm sea level equivalent or 16 ± 4% of mass stored in Icelandic glaciers around 1890. Almost half of the total mass change occurred in 1994/95 to 2018/19, or −240 ± 20 Gt (−9.6 ± 0.8 Gt a−1 on average), with most rapid loss in 1994/95 to 2009/10 (mass change rate −11.6 ± 0.8 Gt a−1). During the relatively warm period 1930/31–1949/50, mass loss rates were probably close to those observed since 1994, and in the colder period 1980/81–1993/94, the glaciers gained mass at a rate of 1.5 ± 1.0 Gt a−1. For other periods of this study, the glaciers were either close to equilibrium or experienced mild loss rates. For the periods of AR6 IPCC, the mass change rates are −3.1 ± 1.1 Gt a−1 for 1900/01–1989/90, −4.3 ± 1.0 Gt a−1 for 1970/71–2017/18, −8.3 ± 0.8 Gt a−1 for 1992/93–2017/18, and −7.6 ± 0.8 Gt a−1 for 2005/06–2017/18.